Neuropsychiatric or Behavioral and Psychological Symptoms of Dementia (BPSD): Focus on Prevalence and Natural History in Alzheimer's Disease and Frontotemporal Dementia - Laganà, Valentina; Bruno, Francesco; Altomari, Natalia; Bruni, Giulia; Smirne, Nicoletta; Curcio, Sabrina; Mirabelli, Maria; Colao, Rosanna; Puccio, Gianfranco; Frangipane, Francesca; Cupidi, Chiara; Torchia, Giusy; et al. (Frontiers in Neurology, 2022)
Neuropsychiatric or Behavioral and Psychological Symptoms of Dementia (BPSD) represent a heterogeneous group of non-cognitive symptoms that are virtually present in all patients during the course of their disease. The aim of this study is to examine the prevalence and natural history of BPSD in a large cohort of patients with behavioral variant of Frontotemporal Dementia (bvFTD) and Alzheimer’s Disease (AD) in three stages: i) pre-T0 (before the onset of the disease); ii) T0 or Manifested Disease (from onset to 5 years); iii) T1 or Advanced (from 5 years onwards).Six hundred seventy four clinical records of bvFTD patients and 1925 with AD, from 2006 to 2018, were studied. Symptoms have been extracted from Neuropsychiatric Inventory (NPI) and from a checklist of BPSD for all periods observed. In our population, BPSD affect up to 90% of all dementia subjects over the course of their illness. BPSD profiles of the two dementia groups were similar but not identical. The most represented symptoms were apathy, irritability/affective lability and agitation/aggression. Considering the order of appearance of neuropsychiatric symptoms in AD and bvFTD, mood disorders (depression, anxiety) come first than the other BPSD, with the same prevalence. This means that they could be an important “red flag” in detection of dementia. With the increase of disease severity, aberrant motor behavior and wandering were significantly more present in both groups. Differences between BPSD in AD and bvFTD resulted only in prevalence: systematically, in bvFTD all the symptoms were more represented than in AD, except for hallucinations, depression, anxiety and irritability. Given their high frequency and impact on management and overall health care resources, BPSD should not be underestimated and considered as an additional important diagnostic and therapeutic target both in AD and bvFTD patients.